2016
DOI: 10.1152/ajpregu.00149.2015
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglyceride physiology in the short-finned eel, Anguilla australis—the effects of androgen

Abstract: The importance of androgens (especially 11-ketotestosterone) during previtellogenesis in eels is well established. In wild pubertal migrants, circulating 11-ketotestosterone levels correlate with a number of morphological and molecular changes. Here, we test the prediction that this correlation represents a causal relationship by artificially raising the levels of circulating 11-ketotestosterone in prepubertal nonmigratory female and pubertal, migratory male short-finned eels (Anguilla australis) using sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Many years of research have seen Japanese scientists succeed in completing the life cycle of the Japanese eel, but problems with egg quality and larval feed have been cited as factors that limit mass production of seedlings for aquaculture or stock enhancement purposes (e.g., Okamura et al, 2014;Izumi et al, 2016). We posed that androgen treatment, previously seen to shorten the duration of fertility treatment in shortfinned eels (Lokman et al, 2015), might be effective in modulating egg quality, given that androgens have wide-ranging effects on ovarian lipid physiology (Divers et al, 2010;Endo et al, 2011;Damsteegt et al, 2016) and on expression of the Fsh receptor (Setiawan et al, 2012) in anguillids. The present study provides support for this prediction, as reflected in increased fertilization, hatching and survival rates of eel larvae produced from androgen-treated maternal parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many years of research have seen Japanese scientists succeed in completing the life cycle of the Japanese eel, but problems with egg quality and larval feed have been cited as factors that limit mass production of seedlings for aquaculture or stock enhancement purposes (e.g., Okamura et al, 2014;Izumi et al, 2016). We posed that androgen treatment, previously seen to shorten the duration of fertility treatment in shortfinned eels (Lokman et al, 2015), might be effective in modulating egg quality, given that androgens have wide-ranging effects on ovarian lipid physiology (Divers et al, 2010;Endo et al, 2011;Damsteegt et al, 2016) and on expression of the Fsh receptor (Setiawan et al, 2012) in anguillids. The present study provides support for this prediction, as reflected in increased fertilization, hatching and survival rates of eel larvae produced from androgen-treated maternal parents.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some benefits of androgen treatment prior to administration of pituitary homogenates to female Japanese eels (Anguilla japonica; Matsubara et al, 2003a,b) and Australian shortfinned eels, A. australis (Lokman et al, 2015), were reported, but effects on egg quality (fertilization and hatching rates) were not investigated. Androgens have notable impacts on lipid physiology in eel (c.f., Divers et al, 2010;Damsteegt et al, 2016) and egg quality in several fish species is known to be affected by lipid content and/or composition. Therefore, we predicted that co-treatment of androgens and pituitary homogenates might affect the quality of eggs from artificially matured European eels, A. anguilla.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, administration of 11KT implants to prepubertal female shortfinned eels led to sustained elevation of serum 11KT levels accompanied by increased hepatosomatic index and transcript copy numbers of Apob and Mtp, along with elevated serum TAG, suggesting that 11KT also acts to stimulate repackaging of endogenous TAG for export to the ovary (Damsteegt et al, 2016). (see also Section V.B.…”
Section: Previtellogenic Secondary Follicle Developmentmentioning
confidence: 94%
“…Similarly, exposure to DRO changes plasmatic levels of steroids in juvenile sea bass by decreasing the concentrations of 17-hydroxypregnenolone, 17hydroxyprogesterone and androstenedione after 30 days exposure to 10 ng•g -1 DRO through the diet (Blanco et al, 2016). Thus, although further research is needed, one may hypothesize that DRO and other endocrine disrupters, by modulating the synthesis of androgens and other endogenous steroids may interfere with lipid and TG homeostasis as described by Damsteegt et al (2016), who revealed androgens as major regulators of TG physiology in eels.…”
Section: Discussionmentioning
confidence: 98%